2014
DOI: 10.4103/1463-1741.140499
|View full text |Cite
|
Sign up to set email alerts
|

Activity of coenzyme Q10(Q-Ter multicomposite) on recovery time in noise-induced hearing loss

Abstract: A potential consequence of exposure to noise is a temporary reduction in auditory sensitivity known as temporary threshold shift (TTS), which mainly depends on the intensity and duration of exposure to the noise. Recovery time is related to the amount of initial hearing loss, and the most recovery takes place during the first 15 min following exposure. This study evaluated the efficacy in otoprotection against noise-induced hearing loss of an orally administrated food supplement containing coenzyme Q 10 -Ter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Coenzyme Q10 is a potent antioxidant by either directly scavenging free radicals or recycling and regenerating other antioxidants [ 33 , 34 ]. Noteworthy, Qter ® showed enhanced bioavailability with respect to the native form [35] and demonstrated a protective effect in preventing damage to the outer hair cells of the cochlea following noise exposure [ 8 , 10 , 12 ]. Likewise, Ginkgo biloba extract has demonstrated to prevent gentamicin and cisplatin-induced ototoxicity in both in-vitro and animal models [ 36 , 37 ], as well as to protect cochlear hair cells against ototoxicity induced by gentamicin through the reduction of ROS and nitric oxide-related apoptosis [37] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coenzyme Q10 is a potent antioxidant by either directly scavenging free radicals or recycling and regenerating other antioxidants [ 33 , 34 ]. Noteworthy, Qter ® showed enhanced bioavailability with respect to the native form [35] and demonstrated a protective effect in preventing damage to the outer hair cells of the cochlea following noise exposure [ 8 , 10 , 12 ]. Likewise, Ginkgo biloba extract has demonstrated to prevent gentamicin and cisplatin-induced ototoxicity in both in-vitro and animal models [ 36 , 37 ], as well as to protect cochlear hair cells against ototoxicity induced by gentamicin through the reduction of ROS and nitric oxide-related apoptosis [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants, ROS scavengers, or anti-inflammatory drugs may thus represent potential therapeutic options to prevent platinum-associated ototoxicity. Among these, the supplementation of water-soluble coenzyme Q10 (Q10 terclatrate − QTer ® ) was already able to prevent in animals [ 7 , 8 , 9 , 10 ] and human volunteers [ 11 , 12 ] both noise-induced hear loss (NIHL) and gentamycin mediated ototoxicity, which have a similar ROS mediated etiology. Moreover, the same strategy was reported to exert significant improvements of hearing thresholds at 1000 Hz, 2000 Hz, 4000 Hz, and 8000 Hz in patients with presbycusis [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other antioxidants that can potentially play a protective role against noise-induced cochlear trauma include ginseng [172], co-enzyme Q10 [177], as well as several vitamins, such as vitamin A [178], vitamin C [179, 180], vitamin E [181, 182], and vitamin B12 [183]. Studies in animals showed a protective benefit from combination antioxidant treatment, such as magnesium and vitamin A, C, and E [184], possibly due to synergistic effects [185187], These studies were mainly performed in animals or in small groups of humans and the results should be considered preliminary.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…Protection was achieved only using the 10-day pre-noise dosing strategy; no reductions in TTS were achieved with 1-hour pre-noise dosing. Finally, Staffa et al [2014] reported reductions in TTS induced by unilateral exposure to narrow-band noise using 30-day pre-treatment with coenzyme Q10, in addition to 8 other active agents including lactium, melatonin, choline, Ginkgo biloba, and vitamins E, B 1 , B 6 , and B 12 . When the treatment period was shorter (7 days pre-noise) and the supplement included only coenzyme Q10, TTS induced by white noise was not reduced although noise-induced decreases in distortion product otoacoustic emission (DPOAE) amplitude were ameliorated [Fetoni et al, 2009].…”
Section: Introductionmentioning
confidence: 99%